The Role of District Governments in Handling Damage to National Roads in the Regional Autonomy - Iswantoro, Iswantoro; Saparwadi, Saparwadi; Triasari, Devi (Lembaga Contrarius Indonesia, 2024)
The problematic reality of national roads in rural and urban areas is that they are often damaged and unfit for use. This is due to nationwide road repairs that rely only on the central government's responsibility, resulting in development delays that could endanger the safety of road users. The method used in this research is social legal research to observe law in the dynamics of social life in the context of the role of district and city governments in dealing with damage to national roads. The role of the government in dealing with damage to national roads is to carry out supervision to prevent workers from committing irregularities, misappropriation, and wastage of funds, as well as to overcome obstacles that may occur during the repair process. In addition, the government has a role in carrying out road construction and accommodating policies regarding road construction. Thus, even though national roads are the responsibility of the central government, district and city governments also need to take responsibility for national roads.